Mechanisms of Development and Clinical Significance of Anemia in Patients with Type 1 and Type 2 Diabetes Mellitus (Eurasian Medical Research Periodical, 2023)
Diabetes mellitus (DM) is a common disease that affects about 5% of the European population. The prevalence of this disease is increasing every year. It is expected that in the next few years the number of such patients in Europe will exceed 32 million people. A characteristic complication of both type 1 and type 2 diabetes is nephropathy. In industrialized countries, diabetic nephropathy has now become the leading cause of end-stage chronic kidney disease (CKD). As the number of patients with DM increases, we can expect a proportional increase in the role of diabetic nephropathy in the structure of patients with terminal renal insufficiency